Organic and inorganic nitrogen source ratio effects on Bacillus thuringiensis var.israelensis delta-endotoxin production - Avignone Rossa, Claudio Adolfo (1990)
The influence of different organic and inorganic nitrogen source combinations and C∶N ratios was studied in connection with growth and protein production of Bacillus thuringiensis var.israelensis. Protein production was assumed to be proportional to delta-endotoxin production. Delta-endotoxin concentration increased when media were supplemented with (NH4)2SO4, but the delta-endotoxin: biomass dry weight ratio was unaffected by different C∶N ratios. Organic nitrogen source, yeast extract, could be partially replaced by (NH4)2SO4 with a significant increase in delta-endotoxin production.